Assessment of medical students’ Surgery knowledge based on Progress Test - Filho, Pedro Tadao Hamamoto [UNESP] (2023)
Progress Testing (PT) is an assessment tool whose use has grown throughout Brazil in the last decade. PT makes it possible to assess the students’ knowledge gain throughout the undergraduate course and, for their interpretations to be valid, their items (questions) must have adequate quality from the point of view of content validity and reliability of results. In this study, we analyzed the psychometric characteristics of the items and the performance of students in the content area of surgery from 2017 to 2023. For the analyses, we used the assumptions of Classical Test Theory, Bloom’s taxonomy and Cronbach’s alpha reliability coefficient. The items were easy (average difficulty index between 0.3-0.4), with fair to good discrimination (discrimination index between 0.3-0.4) and with a predominance of medium to high taxonomy. Reliability remained substantial over the years (>0.6). Students’ knowledge gain in surgery was found to be progressive and more important from the 3rd year of the undergraduate course, reaching approximately 70-75% in the 6th year. This measurements framework can be replicated in other contexts for a better understanding of student learning and for qualification of evaluation processes.